Characteristics of Suicides Caused by Drug Overdose in the State of Maryland - Ling Li; Xinbiao Liao; Guozhong Zhang; Daming Sun; Tiantong Yang; Keming Yun; Rebecca Phipps; Xiang Zhang; Mary G Ripple; David Fowler (Wolters Kluwer Medknow Publications, 2015)
Suicidal drug overdose is a major public health issue. In the United States, every year more than 33,000 people commit suicides. Our study focused on the characteristics of suicide victims in the state of Maryland. Material and methods: This study was a retrospective review of autopsy cases of all suicide deaths caused by drug (s) or drug (s) with alcohol intoxication investigated by the OCME in Maryland over a 7-year period from January 2004 to December 2011. All deaths investigated by the OCME that require autopsy examination are subject to comprehensive toxicology testing for drugs and alcohol. The screen tests were performed using gas chromatography (GC) and radioimmunoassay techniques. All detected drugs and/or metabolites were confirmed using GC-mass spectrometry (GC-MS). Results: From 2004 to 2011, 434 deaths were certified as suicide. Of the 434 suicidal overdose deaths, 84% were white, 11% were African-American, and about 5% were either Hispanic or Asian. The male and female ratio was almost equal. Their ages ranged 15-82 years. Of the 434 suicidal drug overdose deaths, 277 victims (63.8%) consumed a single drug type and 157 (36.2%) consumed more than one type of drug. Of the 277 single-drug overdose cases, 71.1% suicides were due to prescription drugs, 23.5% due to over-the-counter drugs, and 5.4% due to street/recreational drugs. Among single-type prescription drugs, analgesic (N = 76), antidepressant (N = 45), and neuroleptic (N = 35) classes were the three leading type of drugs used in suicidal deaths. Oxycodone, morphine, quetiapine, and amitriptyline were the most common prescription drugs in suicidal overdose. Diphenhydramine was the leading over-the-counter drug. Of the 157 victims who consumed more than one drug, combined prescription drugs were present in 54.1%, mixed prescription and over-the-counter drugs in 29.3%, and prescription drugs/over-the-counter drugs and street drugs in 16.6% of cases. Of the multiple-drug overdose suicides, 66.2% cases involved antidepressants. Discussion: Suicide is found in every age, racial, and ethnic group. In the USA, poisoning is thethird-leading method of suicide, following firearm injuries and hanging/strangulation. Our study indicates that prescription drugs, such as those in the opioid analgesic, neuroleptic, and antidepressant class (e.g., oxycodone, morphine, quetiapine, amitriptyline, doxepin, and citalopram), are of special concern in the context of suicidal overdose deaths in the state of Maryland. Therefore, addressing the problems of intentional drug overdose in our society is worthy of public attention.